A repudiatory breach in the construction industry - non-payment - Lee, Shih Yin (2007)
Many complaints have been voiced about non-payments and it is causing severe cash flow problems to contractors. The reaction of many contractors when faced with non-payment is to consider stopping work on site. Whilst this is understandable in many instances, it may amount to a repudiatory breach by the contractor. The contractors are only entitled to terminate the contract when nonpayment is a repudiation of contract. But is the act of non-payment goes to the root of the contract? Whether failure to pay amounts to repudiation will depend on the circumstances of the case. Therefore, this study is to identify circumstances where non-payment by an employer constitutes a repudiatory breach of contract. Findings of this study will assist the contractor to understand his position before he takes action when the employer fails to make payment. The approach adopted in this research is case law based; only cases specifically centered on issue of non-payment will be discussed in this study. The selection of sample court cases involved a depth study rather than a random sample. A total number of 11 cases were studied, where 7 of them were involving construction contracts and 4 were contracts of sales of goods. It is found that there are 2 circumstances in which non-payment constitutes to repudiatory breach and 9 circumstances in which non-payment does not amount to repudiation of the contract. As a conclusion, the result of the analysis seems to suggest that, in most of the circumstances, non-payment is not a repudiatory breach of contract by the employer. The contractors are not advised to stop work at the site when the employer refused to make payments, or he himself would be guilty of a breach of contract in failing to maintain regular and diligent progress. But, an employer may be held to be in repudiatory breach of contract in failing to make payment if his action shows an intention no longer to be bound by the contract and his default goes to the root of the contract.